Baboon envelope pseudotyped lentiviral vectors efficiently transduce human B cells and allow active factor IX B cell secretion in vivo in NOD/SCIDγc‐/‐ mice. (8th November 2016) - Levy, C.; Fusil, F.; Amirache, F.; Costa, C.; Girard‐Gagnepain, A.; Negre, D.; Bernadin, O.; Garaulet, G.; Rodriguez, A.; Nair, N.; Vandendriessche, T.; Chuah, M.; et al.
Abstract : Essentials B cells are attractive targets for gene therapy and particularly interesting for immunotherapy. A baboon envelope pseudotyped lentiviral vector (BaEV‐LV) was tested for B‐cell transduction. BaEV‐LVs transduced mature and plasma human B cells with very high efficacy. BaEV‐LVs allowed secretion of functional factor IX from B cells at therapeutic levels in vivo . Summary: Background: B cells are attractive targets for gene therapy for diseases associated with B‐cell dysfunction and particularly interesting for immunotherapy. Moreover, B cells are potent protein‐secreting cells and can be tolerogenic antigen‐presenting cells. Objective: Evaluation of human B cells for secretion of clotting factors such as factor IX (FIX) as a possible treatment for hemophilia. Methods: We tested here for the first time our newly developed baboon envelope (BaEV) pseudotyped lentiviral vectors (LVs) for human (h) B‐cell transduction following their adaptive transfer into an NOD/SCIDγc ‐/‐ (NSG) mouse. Results: Upon B‐cell receptor stimulation, BaEV‐LVs transduced up to 80% of hB cells, whereas vesicular stomatitis virus G protein VSV‐G‐LV only reached 5%. Remarkably, BaEVTR‐LVs permitted efficient transduction of 20% of resting naive and 40% of resting memory B cells. Importantly, BaEV‐LVs reached up to 100% transduction of human plasmocytes ex vivo . Adoptive transfer of BaEV‐LV‐transduced mature B cells into NOD/SCID/γc ‐/‐ (NSG) [non‐obese diabetic (NOD), severe combined immuno‐deficiency (SCID)] mice allowed differentiation into plasmablasts and plasma B cells, confirming a sustained high‐level gene marking in vivo . As proof of principle, we assessed BaEV‐LV for transfer of human factor IX (hFIX) into B cells. BaEV‐LVs encoding FIX efficiently transduced hB cells and their transfer into NSG mice demonstrated for the first time secretion of functional hFIX from hB cells at therapeutic levels in vivo . Conclusions: The BaEV‐LVs might represent a valuable tool for therapeutic protein secretion from autologous B cells in vivo in the treatment of hemophilia and other acquired or inherited diseases.